PTFE-assisted immobilization of Pluronic F127 in PVDF hollow fiber membranes with enhanced hydrophilicity through nonsolvent-thermally induced phase separation method - Zhao, Jie (2021)
The use of amphiphilic copolymer Pluronic F127 as an additive has shown effectiveness in fabricating polyethersulfone (PES) membranes with excellent antifouling properties due to its roles in enhancing pore structure and surface hydrophilicity. However, F127 was found to be unstable in polyvinylidene fluoride (PVDF) membranes as its hydrophilic modifying function was deactivated over time. In present work, we developed a novel approach to immobilize F127 in PVDF hollow fiber membranes using polytetrafluoroethylene (PTFE) particles as a binding agent through the combined nonsolvent and thermally induced phase separation (N-TIPS) method. The results suggest that the hydrophobic segment of F127 could adsorb firmly onto PTFE with the hydrophilic segments protruding outwards. The dual-functions of F127 were observed in pore formation and surface hydrophilization for PVDF membranes. The water contact angle of PVDF/PTFE/F127 membranes decreased from 102 ± 4° to 76 ± 3° compared with membranes without additives. The resultant membranes possess a pure water permeability (PWP) of 869 ± 39 L m−2h−1bar−1 with a mean pore size of 0.09 ± 0.01 μm and an outstanding tensile strength of 7.0 ± 0.3 MPa, suggesting the potential of N-TIPS method for tuning the membrane pore structure and hydrophilicity by using multifunctional additives.